Screening of Amylolytic Bacteria from Mina Padi Aquaculture in Panembangan Village, Cilongok District, Banyumas, Central Java: Screening of Amylolytic Bacteria from Mina Padi Aquaculture - Ayal, Esther Lourence Brendha; Kasprijo, Kasprijo; Fitriadi, Ren; Ryandini, Dini; Nurhafid, Mohammad; Riady, Reza Muhammad; Anandasari, Mira Adyla (Journal of Aquaculture and Fish Health, 2024)
Amylolytic bacteria play an important role in the ecosystem, especially as probiotic and bioremediation agents in cultivation, as examples can be found in Mina Padi culture. The purpose of this study was to determine the amylolytic bacteria in the waters of the Mina Padi pond. Bacterial isolation began with bacterial sampling, inoculation and isolation of bacteria, calculation of the total abundance of bacteria, observation of bacterial morphology and bacterial purification, and isolation of amylolytic bacteria. The results of the isolation of amylolytic bacteria obtained 3 bacterial isolates capable of producing amylolytic enzymes, namely BA5, BA6, and BA7. The highest index of amylolytic activity was obtained by isolates of BA6 with a medium category of 2.3 cm, and the lowest index was obtained by BA5 with a weak category of 0.3 cm. The average bacterial abundance from each dilution was 2.5 x 103 CFU/mL.